Miguel de Unamuno’s political thought: its relationship with Liberalism (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
Recent studies on Unamuno’s political thought have assigned it to liberalism without inserting his thought in the historical development of liberal thought. That is why in this article we undertake a review of Unamuno’s liberalism, locating his ideas in the history of liberal thought. This will lead us to qualify the political labels that have been placed on Unamuno, as well as to reach the following conclusions: 1) Unamuno lacked a deep knowledge of liberalism as it was consolidated in the political philosophy of his time; 2) his liberalism oscillates between social liberalism and individualistic liberalism, 3) tending in the thirties to the individualistic liberalism of Mill and Spencer, precursor of liberal conservatism.